Picturing Russia's men : masculinity and modernity in 19th-century painting - Leigh, Allison, 1983- ("Art & Visual Culture 2020., 2020)
"The sense of estrangement felt by men during the nineteenth century has been called many things - a crisis in masculinity, the mal de siècle, even a psychological disorder known as neurasthenia - but as a phenomenon, such masculine discontent has gone largely unexplored outside of the western European and American contexts. In this ground-breaking new investigation, Allison Leigh explores how Russian painters sought to depict the new psychological struggles associated with modernity and the implications such visual manifestations of anxiety had for masculinity at the time. Drawing on a wide variety of source material, including previously untranslated letters, journals, and contemporary criticism, Leigh investigates how men's lives changed as they experienced the cultural upheavals of the nineteenth century. In so doing, she introduces readers to Russian artists such as Pavel Fedotov, Karl Briullov, Il'ia Repin, and Ivan Kramskoi, all of whom produced masterpieces of realist art in dialogue with paintings made in European artistic centers at the time. The result is a more culturally discursive account of art-making in the nineteenth century, one that challenges some of the enduring myths of masculinity and provides a fresh interpretive history of what constitutes modernism in the history of art"--